Physiotherapy in early stimulation in Down Syndrome: A review study (Research, Society and Development, 2023)
Introduction: Down Syndrome consists of a genetic alteration characterized by the presence of an additional chromosome 21 in all cells of the individual's body, causing them to present several specific physical and mental characteristics, in addition to delays in motor development. In relation to early stimulation, it is a therapeutic technique that addresses various stimuli that can interfere with children's maturity, in order to encourage and facilitate postures that will help develop the motor and cognitive side of children with some limitations, such as Syndrome of Down. Objective: To elucidate evidence that confirms the benefits of early stimulation for children with Down Syndrome. Methodology: This is an integrative literature review, through the analysis and study of articles published in indexed journals, between the years 2018 and 2022, using as reference the databases National Library of Medicine (MEDLINE), Scientific Eletrônic Library Online (SCIELO) and Google Scholar. Results and discussion: The authors of this review contributed substantially to the concept that stimulation can intervene in the child's maturation and facilitate postures that favor the motor and cognitive development of children with Down Syndrome. Conclusion: It was evident that early stimulation is essential for the neural and global maturation of motor development in children with Down syndrome.